Dye Sequestration Using Biosynthesized Silver Nanoparticles Adsorbent in Aqueous Solutions - Madiha Batool; Walid M. Daoush; Muhammad Khalid Hussain (Crystals, 2022)
Nanomaterials have gained much attention in the field of environmental remediation, largely due to their high surface area-to-volume ratio and other unique physical, chemical, and biological characteristics that emerge due to its size effects. Metallic nanoparticles are traditionally manufactured using wet chemical processes; however, the chemicals utilized are generally hazardous and combustible. The biosynthesis of nanoparticles using a variety of plant resources is considered a green technology because it does not use toxic chemicals. This work focuses on the green synthesis of biogenetic silver nanoparticles and their use in the sequestration of colorants from aqueous solution. The extract of aquatic macrophyte Salvinia molesta (water hyacinth) has been employed to prepare silver nanoparticles by chemical reduction reaction. In the UV-visible spectrum of the synthesized silver nanoparticles, the absorbance peak was detected in the 420–430 nm range. The synthesized silver nanoparticles were used to sequester methylene blue (MB) dye in aqueous solution. About 121.04 mg/g was found as the highest adsorption capacity of methylene blue dye on the silver nanoparticles according to the Langmuir isotherm. It was observed that the experimental results and the pseudo-second order kinetics are in good agreement. As a result, the biosynthesized silver nanoparticle might be a potential adsorbent material in the field of environmental rehabilitation and cleanup.